2015
DOI: 10.1002/anie.201507723
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Photonic Capsules Containing Cholesteric Liquid Crystals with Planar Alignment

Abstract: Cholesteric liquid crystals (CLCs) reflect selected wavelengths of light owing to their periodic helical structures. The encapsulation of CLCs leads to photonic devices that can be easily processed and might be used as stand-alone microsensors. However, when CLCs are enclosed by polymeric membranes, they usually lose their planar alignment, leading to a deterioration of the optical performance. A microfluidics approach was employed to integrate an ultrathin alignment layer into microcapsules to separate the CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…[1] Furthermore,the structures and topologies of these colloidal particles are scientifically very interesting. [3] Aßhoff et al recently showed that superstructures of photoresponsive chiral nematic microspheres prepared in am icrofluidic device are promising for chiroptical switches and distributors. [3] Aßhoff et al recently showed that superstructures of photoresponsive chiral nematic microspheres prepared in am icrofluidic device are promising for chiroptical switches and distributors.…”
mentioning
confidence: 99%
“…[1] Furthermore,the structures and topologies of these colloidal particles are scientifically very interesting. [3] Aßhoff et al recently showed that superstructures of photoresponsive chiral nematic microspheres prepared in am icrofluidic device are promising for chiroptical switches and distributors. [3] Aßhoff et al recently showed that superstructures of photoresponsive chiral nematic microspheres prepared in am icrofluidic device are promising for chiroptical switches and distributors.…”
mentioning
confidence: 99%
“…It would be possible to utilize the photo-control of the LC double emulsion for the purpose of active matter, in which it is expected that the force and the direction of the long-ranged molecular interaction should be controlled. To generate a larger force, a LC polymer would be a promising material, which can induce a macroscopic motion such as bending for a film [15]. Furthermore, this study would give more information on the dynamics of the defect behavior of LCs, which would be relevant to various biological phenomena on a cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the color control of a cholesteric liquid crystal droplet with photo-responsive chiral dopant was reported, and the color ranged from blue to red [12,13], and also it was demonstrated for the lasing application [14]. By encapsulating this LC droplet with a polymer core, the coloring particle was successfully developed [15].…”
Section: Introductionmentioning
confidence: 99%
“…The shell geometry also has the advantage that polymer stabilisation of the CLC works very well, making the spheres mechanically robust with minimum negative effect on the optical properties. Another possibility of ensuring robustness is to encapsulate a CLC droplet inside a transparent elastomer shell [29,30].…”
Section: Introductionmentioning
confidence: 99%